Bioavailable insulin-like growth factor-I as mediator of racial disparity in obesity-relevant breast and colorectal cancer risk among postmenopausal women. Issue 3 (March 2017) - Jung, Su Yon; Barrington, Wendy E.; Lane, Dorothy S.; Chen, Chu; Chlebowski, Rowan; Corbie-Smith, Giselle; Hou, Lifang; Zhang, Zuo-Feng; Paek, Min-So; Crandall, Carolyn J.
Abstract: Objective: Bioavailable insulin-like growth factor-I (IGF-I) interacts with obesity and exogenous estrogen (E) in a racial disparity in obesity-related cancer risk, yet their interconnected pathways are not fully characterized. We investigated whether circulating bioavailable IGF-I acted as a mediator of the racial disparity in obesity-related cancers such as breast and colorectal (CR) cancers and how obesity and E use regulate this relationship. Methods: A total of 2, 425 white and 164 African American (AA) postmenopausal women from the Women's Health Initiative Observational Study were followed from October 1, 1993 through August 29, 2014. To assess bioactive IGF-I as a mediator of race-cancer relationship, we used the Baron-Kenny method and quantitative estimation of the mediation effect. Results: Compared with white women, AA women had higher IGF-I levels; their higher risk of CR cancer, after accounting for IGF-I, was no longer significant. IGF-I was associated with breast and CR cancers even after controlling for race. Among viscerally obese (waist/hip ratio >0.85) and overall nonobese women (body mass index <30), IGF-I was a strong mediator, reducing the racial disparity in both cancers by 30% and 60%, respectively. In E-only users and nonusers, IGF-I explained the racial disparity in CR cancer only modestly. Conclusions: Bioavailable IGF-I is potentially important in racial disparities in obesity-related breast and CR cancer risk between postmenopausal AA and white women. Body fat distribution and E use may be part of the interconnected hormonal pathways related to racial difference in IGF-I levels and obesity-related cancer risk. Abstract : Supplemental Digital Content is available in the text